2013
DOI: 10.5812/jjm.5191
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of Hepatitis C Virus Genotypes Among Chronic Infected Injecting Drug Users in Tehran, Iran

Abstract: Background: Hepatitis C virus (HCV) is the main cause of infection that has the potential to cause chronic liver disease. Injecting drug users (IDUs) have a key role in HCV transmission in Iran. Knowledge of the distribution of various genotypes is essential for successful future research and control strategies.Objectives: The aim of this study was to identify HCV genotypes among chronic infected injecting drug users (IDUs) in Tehran, Iran.Patients and Methods: In this cross sectional study, we investigated HC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 20 publications
0
10
0
Order By: Relevance
“…However, in the current study, no association was observed between distinct HCV genotype and age, or HCV risk factors such as IVDA or blood transfusion. On the other hand, recent studies showed that HCV genotype 3a in IVD abusers and HCV genotype 1a in patients receiving blood or blood products were the most common genotypes (14,(49)(50)(51)(52). As shown in Table 2, genotype 3a was not the most frequent genotype just in IVDA donors.…”
Section: Discussionmentioning
confidence: 88%
“…However, in the current study, no association was observed between distinct HCV genotype and age, or HCV risk factors such as IVDA or blood transfusion. On the other hand, recent studies showed that HCV genotype 3a in IVD abusers and HCV genotype 1a in patients receiving blood or blood products were the most common genotypes (14,(49)(50)(51)(52). As shown in Table 2, genotype 3a was not the most frequent genotype just in IVDA donors.…”
Section: Discussionmentioning
confidence: 88%
“…The transmission of HCV occurs mainly through infected blood, blood products, and contaminated devices, such as syringes and needles. Today, intravenous drug use is an important route of HCV transmission ( 4 , 61 ). Precise data about the pattern of HCV genotypes and continuous monitoring of the genetic diversity of virus isolates, especially among high-risk individuals (hemophilia, thalassemia, hemodialysis, multiply transfused patients and intravenous drug use) is essential for understanding HCV epidemiology ( 33 ).…”
Section: Discussionmentioning
confidence: 99%
“…Prevalence of HCV among patients on hemodialysis was 5.5% to 55.9% in different cities of Iran, although this number for patients with hemophilia was 15.65 to 76.7% ( 3 ). The rate of HCV positivity among IVDUs was 52% in Tehran ( 4 ).…”
Section: Contextmentioning
confidence: 99%
See 1 more Smart Citation
“…I read with interest the published article by Ranjbar Kermani et al ( 1 ). Genotyping of hepatitis C virus (HCV) is important, which provides information about strain variation and characteristics of virus during the treatment and the therapy response rate ( 2 ).…”
mentioning
confidence: 99%